The first outbreak: origin of humanism - Baraona Cockerell, Miguel David (2021)
In the 5th century BC arose in Athens and then spread to almost all of ancient Greece, an ethical-philosophical movement with a strong orientation to political philosophy, which is known as sophism and/or sophistry.  The two most prominent figures of sophism would be, Protagoras in the intellectual field, and Pericles in the political field.  But a large group of other philosophers would make sophism the greatest pre-Socratic intellectual revolution in classical Greece.  These progressive philosophers would push for representative democracy, to levels that would later not be known in the ancient world.  And this would lead to social reforms typical of a welfare State, as consigned in the Constitution that Protagoras drafted for the new colony of Thurios.  But the most important aspect is that sophism laid the foundations for the very audacious idea in those times, that the human being (in the form of the common citizen) is the only protagonist in choosing and forging his individual and collective destiny, even though destiny may not be achieved fully and in the desired manner.  This radical turn, placing the human being at the very center of his own destiny, and outside the ominous forces of divine and supernatural order, is what in the European Renaissance, centuries later, would be called humanism.  The main corollary derived from this premise is that the human being is, par excellence, the forger of his own liberation through his reason and will.  That is to say: the fundamental protagonist of his self-emancipation.